Pendekatan Tektual Kontekstual dan Hemenuetika dalam Penafsiran Al-Qur'an - M Khai Hanif Yuli Edi Z; Basirun Basirun; Feska Ajepri; Zulkipli Jemain (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
Various approaches are needed to reflect the universal values of the Quran in diverse societal contexts. This research aims to depict the use of textual, contextual, and hermeneutical approaches in understanding the Quran, as an effort to comprehend the text within the appropriate context of people's lives. The textual approach primarily focuses on grammatical analysis and literal understanding, while the contextual approach involves understanding the extratextual elements and their connection to the situations and conditions during the revelation of the Quran. The hermeneutical approach emphasizes understanding the text and interpreting its meanings, while recognizing the importance of social, political, cultural, and historical contexts in understanding cultural phenomena. Contextual hermeneutics emphasizes the relationship between the text and the surrounding world.